2018
DOI: 10.1021/acs.est.7b04882
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Persistent Vitamin D Deficiency Alters Cardiopulmonary Responses to Particulate Matter-Enhanced Atmospheric Smog in Adult Mice

Abstract: Early life nutritional deficiencies can lead to increased cardiovascular susceptibility to environmental exposures. Thus, the purpose of this study was to examine the effect of early life persistent vitamin D deficiency (VDD) on the cardiopulmonary response to a particulate matter-enhanced photochemical smog. Mice were fed a VDD or normal diet (ND) after weaning. At 17 weeks of age, mice were implanted with radiotelemeters to monitor electrocardiogram, heart rate (HR), and heart rate variability (HRV). Ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Support for this is found in the chemical analysis, which showed that the concentrations of formaldehyde, glyoxal, and methylglyoxal were twice as high in SA-O 3 than in SA-PM . The greater toxicity of SA-O 3 relative to SA-PM was also confirmed in parallel studies with rodents done in conjunction with the present study that also found that SA-O 3 produced more adverse metabolic, immunologic, and cardiovascular effects than did SA-PM. …”
Section: Discusssionsupporting
confidence: 80%
See 1 more Smart Citation
“…Support for this is found in the chemical analysis, which showed that the concentrations of formaldehyde, glyoxal, and methylglyoxal were twice as high in SA-O 3 than in SA-PM . The greater toxicity of SA-O 3 relative to SA-PM was also confirmed in parallel studies with rodents done in conjunction with the present study that also found that SA-O 3 produced more adverse metabolic, immunologic, and cardiovascular effects than did SA-PM. …”
Section: Discusssionsupporting
confidence: 80%
“…33 The greater toxicity of SA-O 3 relative to SA-PM was also confirmed in parallel studies with rodents done in conjunction with the present study that also found that SA-O 3 produced more adverse metabolic, immunologic, and cardiovascular effects than did SA-PM. [39][40][41] Four out of five comparisons showed that the mutagenic potency of SA-PM was not affected by the presence or absence of S9 or heat-inactivated S9, indicating that the mutagenic activity of SA-PM was generally direct-acting (Table 2). Further support for this is shown by the finding that two out of three comparisons showed no significant difference in the mutagenic potency of SA-PM in the presence of either S9 or HI S9 (Table 2).…”
Section: Discusssion Features Of Atmospheresmentioning
confidence: 99%
“…The LF/HF ratio was determined as an estimate of the relative balance between sympathetic and vagal activity. The time-domain measures included the standard deviation of the normal-to-normal beat interval (SDNN) and the root mean square of successive differences (RMSSD) ( Stratford et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…A few recent studies have examined a beneficial role for vitamin D in alleviating adverse effects of pollution in different contexts. Stratford and colleagues have shown vitamin D deficiency to affect the cardiopulmonary response to polluted air in mice [ 63 ]. In a diesel exhaust particle aggravated mouse model of asthma, Bolcas and colleagues have shown vitamin D to have the capacity to decrease airway hyperresponsiveness and pathological T cell populations in the lungs [ 64 ].…”
Section: Discussionmentioning
confidence: 99%